Method for preparing high-strength low-formaldehyde melamine foam
By using phenolic fibers and phenol in melamine foam, the shortcomings in melamine foam in mechanical properties and flame retardant properties are solved, and the preparation of melamine foam with high strength, low aldehyde and excellent flame retardant properties is achieved.
Patent Information
- Application Number
- CN202411645199.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-14
AI Technical Summary
There is a contradiction between the improvement of mechanical properties of melamine foam and the production process and raw material costs, problems such as loss of flame retardant performance, reduced heat resistance performance, and limited toughening amplitude.
Phenolic fibers are used as reinforced filler material to enhance the melamine foam in situ by reacting with melamine resin, and phenol is added to enhance its mechanical properties and flame retardant properties.
The preparation of high-strength and low aldehyde melamine foam is achieved, and excellent flame retardant properties and low formaldehyde content are maintained, while improving the heat resistance and sound absorption properties of the material.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flame-retardant, heat-insulating melamine foam and preparation thereof, and particularly relates to a method for preparing high-strength, low-aldehyde melamine foam. Background Art
[0002] Melamine foam is a foam material with excellent performance. Compared with traditional foam materials, it has the characteristics of high open porosity, good sound absorption and moisture absorption, and aging resistance. Due to its unique three-dimensional network structure with highly cross-linked triazine rings, it has better flame retardant performance and thermal stability. Due to its special properties, it is widely used in aerospace, building materials, closed trains, battery pack insulation and fire protection and other fields.
[0003] However, the characteristics of melamine foam, such as high hardness, low strength, and easy slag, have greatly limited its application range. In order to broaden its application field, a lot of research has been conducted on the enhancement and toughening of mechanical properties through the modification of melamine foam and the regulation of pore structure, and good results have been achieved. However, there are still some problems, such as the contradiction between the improvement of mechanical properties and the production process and raw material costs, the loss of flame retardant properties, the reduction of heat resistance, and the limited toughening range.
[0004] Phenolic formaldehyde is a formaldehyde-containing material with good flame retardancy, good mechanical properties and low formaldehyde emission. The flame retardancy and mechanical properties of melamine foam can be improved and the formaldehyde content can be reduced by the modification reaction of phenol with melamine and formaldehyde.
[0005] The present invention uses phenolic fiber prepared by wet spinning of melamine resin as a reinforcing filling material to in-situ reinforce melamine foam, and by adding phenol, the mechanical properties and flame retardant properties of the melamine foam can be further improved, and a series of explorations are conducted on the properties of the prepared melamine foam. Summary of the invention
[0006] The invention provides a method for preparing high-strength and low-aldehyde melamine foam, which has simple process and small pollution. The prepared melamine foam can ensure increased strength while maintaining the excellent low-aldehyde and flame retardant properties of the melamine foam.
[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions: The invention comprises the following steps: uniformly mixing phenolic fiber, melamine, phenol and aldehyde compounds, reacting them under weak alkaline conditions, heating them for reaction, cooling them down to obtain expandable melamine resin, uniformly stirring the obtained melamine resin with foaming agents and other foaming substances to obtain foaming liquid, foaming them with microwaves, and aging them at high temperature to obtain melamine foam.
[0008] The present invention provides a method for preparing high-strength low-aldehyde melamine foam, comprising the following steps: (1) Phenolic fiber, melamine, phenol, aldehyde compound and alkaline catalyst are mixed and added to deionized water, the pH is adjusted to weak alkalinity, and the mixture is heated to 85-110°C. After the solution becomes clear, the reaction is continued for 20-60 minutes, and then the mixture is quickly cooled to room temperature in a cold water bath to obtain a expandable melamine resin.
[0009] (2) Mix 100 parts of the melamine resin obtained in step (1) with 4-15 parts of a foaming agent, 1-5 parts of a curing agent and 3-10 parts of an emulsifier by mass, stir the mixture evenly and prepare a foaming liquid. The foaming liquid is subjected to microwave foaming and high-temperature aging to obtain melamine foam.
[0010] In the step (1), the molar ratio of melamine to phenol is 1:(0.1-0.7), the molar ratio of melamine to aldehyde compound is 1:(2-3.5), the mass of phenolic fiber is 1-5% of the mass of melamine, and the mass ratio of melamine to alkaline catalyst is 1:(0.001-0.01).
[0011] In the step (1), the phenolic fiber is primary phenolic fiber or phenolic fiber cured in air at 175° C. for 0.1-3 hours; the aldehyde compound is formaldehyde or propionaldehyde; and the alkaline catalyst is one of sodium hydroxide, potassium hydroxide, triethanolamine, and hexamethylenetetramine.
[0012] In the step (2), the foaming agent is one of n-pentane, isopentane, cyclopentane, n-hexane and cyclohexane.
[0013] In the step (2), the curing agent is one of formic acid, acetic acid, hydrochloric acid, sulfuric acid, and p-toluenesulfonic acid.
[0014] In the step (2), the emulsifier is one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium chloride, dodecyl polyoxyethylene ether, and Tween-80.
[0015] In the step (2), the stirring process uses a high-speed mechanical stirring of 3000 r / min for 40-100 s, the microwave foaming power is 2000-4000 W, and the high-temperature aging is aging at a high temperature environment of 90-130° C. for 1-3 h.
[0016] The beneficial effects of the present invention are: 1. Phenolic fiber and melamine foam are both made of formaldehyde-containing resins, which have better compatibility. During the reaction, the fiber and foam skeleton can be cross-linked without surface treatment of the fiber. The fiber has higher strength, which makes the mechanical properties of melamine foam reinforced by phenolic fiber even better.
[0017] 2. Melamine foam material itself has good sound insulation and heat insulation properties. The in-situ reinforced phenolic fiber further improves the sound absorption performance, making the material perform better in sound insulation and heat insulation applications, such as in building insulation, sound insulation panels and industrial sound insulation equipment, effectively improving energy efficiency and comfort.
[0018] 3. Phenolic fiber has good chemical stability, and the in-situ reinforced melamine foam material shows better corrosion resistance when exposed to chemicals such as acids and organic solvents.
[0019] 4. The addition of phenol increases the stability of the groups and methylene groups that react with formaldehyde, reduces the formaldehyde content in melamine foam, and at the same time, the addition of phenol increases the limiting oxygen index, reduces the release of toxic smoke, and increases combustion safety, which makes the material more widely used in chemical industry, anti-corrosion engineering, home decoration and transportation tools. DETAILED DESCRIPTION
[0020] The present invention will be further described below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention, and those skilled in the art in this field can make some non-essential improvements and adjustments based on the content of the above invention.
[0021] Example 1 This embodiment provides a method for preparing high-strength low-aldehyde melamine foam, the steps are as follows: (1) Primary phenolic fiber with a melamine mass fraction of 1% was mixed with melamine, phenol and formaldehyde, and added to deionized water. The pH was adjusted to a weak alkaline state by adding an alkaline catalyst, sodium hydroxide, and heated to 85°C. After the solution became clear and transparent, the reaction was continued at a constant temperature for 20 minutes. The solution was then taken out and quickly cooled to room temperature in a cold water bath to obtain a expandable melamine resin. The molar ratio of melamine to phenol was 1:0.1, the molar ratio of melamine to aldehyde compounds was 1:2, and the mass ratio of melamine to alkaline catalyst was 1:0.001.
[0022] (2) 100 parts by mass of the obtained expandable melamine resin were mixed with 4 parts of n-pentane, 1 part of formic acid and 3 parts of sodium dodecyl sulfate, and then stirred at 3000 r / min for 40 seconds to prepare a foaming liquid. The foaming liquid was subjected to microwave foaming at a foaming power of 2000 W, and then aged at a high temperature of 90° C. for 1 hour to obtain melamine foam.
[0023] The apparent density of the melamine foam is 4.1 kg / m 3The open porosity is 96%, the tensile strength is 1050kPa, the elongation at break is 52%, the formaldehyde content is 15mg / kg, the sound absorption coefficient of 10cm melamine foam at a frequency of 100Hz-4000Hz reaches 98.5%, the vertical burning UL-94 rating is V-0, the limiting oxygen index is 36.1%, the thermal conductivity is 0.026W / (m·K), and the foam is not easy to fall off. Example 2
[0024] This embodiment provides a method for preparing high-strength low-aldehyde melamine foam, the steps are as follows: (1) Phenolic fiber cured at 175°C for 0.1h in air with a melamine mass fraction of 5% was mixed with melamine, phenol and propionaldehyde and added to deionized water. The pH was adjusted to weak alkalinity by adding alkaline catalyst potassium hydroxide, and heated to 110°C. After the solution became clear and transparent, the reaction was continued at a constant temperature for 60min. Then the solution was taken out and quickly cooled to room temperature in a cold water bath to obtain a expandable melamine resin. The molar ratio of melamine to phenol was 1:0.7, the molar ratio of melamine to aldehyde compounds was 1:3.5, and the mass ratio of melamine to alkaline catalyst was 1:0.01.
[0025] (2) 100 parts by mass of the obtained expandable melamine resin were mixed with 15 parts by mass of isopentane, 5 parts by mass of acetic acid and 10 parts by mass of sodium dodecylbenzene sulfonate, and then stirred at 3000 r / min for 100 s to prepare a foaming liquid, and the foaming liquid was subjected to microwave foaming at a foaming power of 4000 W, and then aged at a high temperature of 130° C. for 3 h to obtain melamine foam.
[0026] The apparent density of the melamine foam is 3.5 kg / m 3 The open porosity is 98%, the tensile strength is 845kPa, the elongation at break is 93%, the formaldehyde content is 10mg / kg, the sound absorption coefficient of 10cm melamine foam at a frequency of 120Hz-4000Hz reaches 98.5%, the vertical burning UL-94 rating is V-0, the limiting oxygen index is 47.1%, the thermal conductivity is 0.017W / (m·K), and the foam is not easy to fall off. Example 3
[0027] This embodiment provides a method for preparing high-strength low-aldehyde melamine foam, the steps are as follows: (1) Phenolic fiber cured at 175°C for 3h in air with a melamine mass fraction of 5% was mixed with melamine, phenol and formaldehyde and added to deionized water, and the pH was adjusted to weak alkalinity by adding alkaline catalyst triethanolamine, and heated to 90°C. After the solution became clear and transparent, the reaction was continued at a constant temperature for 50min, and then the solution was taken out and quickly cooled to room temperature in a cold water bath to obtain a expandable melamine resin. The molar ratio of melamine to phenol was 1:0.6, the molar ratio of melamine to aldehyde compounds was 1:3, and the mass ratio of melamine to alkaline catalyst was 1:0.008.
[0028] (2) 100 parts by mass of the obtained expandable melamine resin were mixed with 4 parts by mass of cyclopentane, 1 part by mass of hydrochloric acid and 5 parts by mass of hexadecyltrimethylammonium chloride, and then stirred at 3000 r / min by a high-speed mechanical stirrer for 80 seconds to prepare a foaming liquid, and the foaming liquid was subjected to microwave foaming at a foaming power of 3000 W, and then aged at a high temperature of 130° C. for 2 hours to obtain melamine foam.
[0029] The apparent density of the melamine foam is 11 kg / m 3 The open porosity is 96%, the tensile strength is 1154kPa, the elongation at break is 31%, the formaldehyde content is 18mg / kg, the sound absorption coefficient of 10cm melamine foam at a frequency of 130Hz-4000Hz reaches 98.8%, the vertical burning UL-94 rating is V-0, the limiting oxygen index is 44.5%, the thermal conductivity is 0.005W / (m·K), and the foam is not easy to fall off. Example 4
[0030] This embodiment provides a method for preparing high-strength low-aldehyde melamine foam, the steps are as follows: (1) Phenolic fiber cured at 175°C for 0.9h in air with a melamine mass fraction of 1% was mixed with melamine, phenol and formaldehyde and added to deionized water. The pH was adjusted to weak alkalinity by adding alkaline catalyst hexamethylenetetramine, and heated to 95°C. After the solution became clear, the reaction was continued at a constant temperature for 60min. Then the solution was taken out and quickly cooled to room temperature in a cold water bath to obtain a expandable melamine resin. The molar ratio of melamine to phenol was 1:0.4, the molar ratio of melamine to aldehyde compound was 1:2, and the mass ratio of melamine to alkaline catalyst was 1:0.002.
[0031] (2) 100 parts by mass of the obtained expandable melamine resin were mixed with 5 parts by mass of n-hexane, 2 parts by mass of sulfuric acid and 3 parts by mass of dodecyl polyoxyethylene ether, and then stirred at 3000 r / min by a high-speed machine for 40 seconds to prepare a foaming liquid, and the foaming liquid was subjected to microwave foaming at a foaming power of 2000 W, and then aged at a high temperature of 90° C. for 2 hours to obtain melamine foam.
[0032] The apparent density of the melamine foam is 9kg / m3 The open porosity is 95%, the tensile strength is 952kPa, the elongation at break is 84%, the formaldehyde content is 15mg / kg, the sound absorption coefficient of 10cm melamine foam at a frequency of 130Hz-4000Hz reaches 98.6%, the vertical burning UL-94 rating is V-0, the limiting oxygen index is 43.1%, the thermal conductivity is 0.016W / (m·K), and the foam is not easy to fall off. Example 5
[0033] This embodiment provides a method for preparing high-strength low-aldehyde melamine foam, the steps are as follows: (1) Phenolic fiber cured at 175°C for 0.3h in air with a 4% melamine mass fraction was mixed with melamine, phenol and propionaldehyde and added to deionized water, and the pH was adjusted to weak alkalinity by adding alkaline catalyst sodium hydroxide, and heated to 85°C. After the solution became clear and transparent, the reaction was continued at a constant temperature for 30min, and then the solution was taken out and quickly cooled to room temperature in a cold water bath to obtain a expandable melamine resin. The molar ratio of melamine to phenol was 1:0.2, the molar ratio of melamine to aldehyde compounds was 1:2.8, and the mass ratio of melamine to alkaline catalyst was 1:0.001.
[0034] (2) 100 parts by mass of the obtained expandable melamine resin were mixed with 12 parts by mass of cyclohexane, 4 parts by mass of p-toluenesulfonic acid and 6 parts by mass of Tween-80, and then stirred at 3000 r / min for 50 seconds to prepare a foaming liquid. The foaming liquid was subjected to microwave foaming at a foaming power of 2500 W, and then aged at a high temperature of 90° C. for 2 hours to obtain melamine foam.
[0035] The apparent density of the melamine foam is 2.5 kg / m 3 The open porosity is 95%, the tensile strength is 857kPa, the elongation at break is 33%, the formaldehyde content is 15mg / kg, the sound absorption coefficient of 10cm melamine foam at a frequency of 130Hz-4000Hz reaches 98.9%, the vertical burning UL-94 rating is V-0, the limiting oxygen index is 38.7%, the thermal conductivity is 0.038W / (m·K), and the foam is not easy to fall off. Example 6
[0036] This embodiment provides a method for preparing high-strength low-aldehyde melamine foam, the steps are as follows: (1) Phenolic fiber cured at 175°C for 0.3h in air with a 3% melamine mass fraction was mixed with melamine, phenol and formaldehyde and added to deionized water, and the pH was adjusted to weak alkalinity by adding alkaline catalyst potassium hydroxide, and heated to 90°C. After the solution became clear and transparent, the reaction was continued at a constant temperature for 35min, and then the solution was taken out and quickly cooled to room temperature in a cold water bath to obtain a expandable melamine resin. The molar ratio of melamine to phenol was 1:0.5, the molar ratio of melamine to aldehyde compounds was 1:2.3, and the mass ratio of melamine to alkaline catalyst was 1:0.006.
[0037] (2) 100 parts by mass of the obtained expandable melamine resin were mixed with 8 parts by mass of n-hexane, 3 parts by mass of formic acid and 6 parts by mass of sodium dodecylbenzene sulfonate, and then stirred at 3000 r / min by a high-speed mechanical stirrer for 90 seconds to prepare a foaming liquid, and the foaming liquid was subjected to microwave foaming at a foaming power of 3600 W, and then aged at a high temperature of 110° C. for 2 hours to obtain melamine foam.
[0038] The apparent density of the melamine foam is 4 kg / m 3 The open porosity is 96%, the tensile strength is 760kPa, the elongation at break is 33%, the formaldehyde content is 15mg / kg, the sound absorption coefficient of 10cm melamine foam at a frequency of 130Hz-4000Hz reaches 98.6%, the vertical burning UL-94 rating is V-0, the limiting oxygen index is 45.2%, the thermal conductivity is 0.007W / (m·K), and the foam is not easy to fall off.
[0039] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing high-strength low-aldehyde melamine foam, characterized in that Here are the steps: (1) Phenolic fiber, melamine, phenol, aldehyde compound and alkaline catalyst are mixed and added into deionized water, pH is adjusted to weak alkalinity, heated to 85-110°C, and after the solution becomes clear and transparent, the reaction is continued for 20-60 minutes, and then quickly cooled to room temperature in a cold water bath to obtain a expandable melamine resin; (2) Mix 100 parts of the melamine resin obtained in step (1) with 4-15 parts of a foaming agent, 1-5 parts of a curing agent and 3-10 parts of an emulsifier by mass, stir the mixture evenly and prepare a foaming liquid. The foaming liquid is subjected to microwave foaming and high-temperature aging to obtain melamine foam.
2. A method for preparing high-strength low-aldehyde melamine foam according to claim 1, characterized in that: In the step (1), the molar ratio of melamine to phenol is 1:(0.1-0.7), the molar ratio of melamine to aldehyde compound is 1:(2-3.5), the mass of phenolic fiber is 1-5% of the mass of melamine, and the mass ratio of melamine to alkaline catalyst is 1:(0.001-0.01).
3. A method for preparing high-strength low-aldehyde melamine foam according to claim 1, characterized in that: In the step (1), the phenolic fiber is primary phenolic fiber or phenolic fiber cured in air at 175° C. for 0.1-3 hours; the aldehyde compound is formaldehyde or propionaldehyde; and the alkaline catalyst is one of sodium hydroxide, potassium hydroxide, triethanolamine, and hexamethylenetetramine.
4. A method for preparing high-strength low-aldehyde melamine foam according to claim 1, characterized in that: In the step (2), the foaming agent is one of n-pentane, isopentane, cyclopentane, n-hexane and cyclohexane.
5. A method for preparing high-strength low-aldehyde melamine foam according to claim 1, characterized in that: In the step (2), the curing agent is one of formic acid, acetic acid, hydrochloric acid, sulfuric acid, and p-toluenesulfonic acid.
6. The method for preparing high-strength low-aldehyde melamine foam according to claim 1, characterized in that: In the step (2), the emulsifier is one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium chloride, dodecyl polyoxyethylene ether, and Tween-80.
7. The method for preparing high-strength low-aldehyde melamine foam according to claim 1, characterized in that: In the step (2), the stirring process uses a high-speed mechanical stirring of 3000 r / min for 40-100 s, the microwave foaming power is 2000-4000 W, and the high-temperature aging is aging at a high temperature environment of 90-130° C. for 1-3 h.